الوسائل العلاجية الطريفة في التراث العلمي العربي: استعمال الأنغام الموسيقية أنموذجاً - سيد، أشرف صالح محمد (جامعة بغداد - مركز إحياء التراث العلمي العربي, 2017)
The scientific heritage is an essential part of the civilization of nation, so Nations has focused on this aspect in the construction of civilization. So the Arab prosperous scientific achievements is no exception to this general rule in being an integral part of the composition of the Arab- Islamic civilization part, and when we read in the Arab–Islamic medicine books, we find the genius of the Arab and Muslims physicians and their own new methods of treatment they use music melodies in medication and treatment of patients. This study aims to highlight that exotic therapeutic method in the Arab scientific heritage, which is practiced by doctors in order to put patients in the right atmosphere to seek healing , it was found that music was one of the most important forms of entertainment practiced by the Arab and Muslim physicians in the treatment of mental diseases. The researcher used the methodology of historical research in this study to tracking what was narrated about that point in sources and references.
إن تراث الأمم، وبخاصة تراثها العلمي يشكل مركبة أساسية في حضارتها، لذلك فقد اهتمت الأمم على اختلاف أجناسها ولغاتها بهذا الجانب في بنائها الحضاري. والتراث العلمي العربي الزاهر بالإنجازات العلمية لا يشذ عن هذه القاعدة العامة في كونه جزء لا يتجزأ من التركيبة الحضارية العربية الإسلامية، فالباحث عن الطب العربي الإسلامي يقف معجبا أمام نبوغ الأطباء العرب والمسلمين وابتكارهم طرائق وأساليب جديدة في العلاج، من ذلك استعمالهم الأنغام الموسيقية في التطبيب وعلاج المرضي. وقد استعان الباحث بمنهج البحث التاريخي في هذه الدراسة لتناول هذا النمط من المعالجة متتبعا ما ورد عنه في الأصول والمراجع، لإبراز تلك الطريقة العلاجية الطريفة في التراث العلمي العربي، والتي مارسها الأطباء بهدف وضع المرضي في الجو الملائم لالتماس الشفاء، حيث تبين أن الموسيقى كانت من أهم الوسائل الترفيهية التي مارسها الأطباء العرب والمسلمون في معالجة الأمراض النفسية. المحور الأول: الطب والصيدلة في التراث.
Keywords: التراث العربي -- التراث العلمي -- العلاج بالموسيقى -- الحضارة الإسلامية